Development of Technology-Based Teaching Materials in Islamic Religious Education Subjects - Suharsiwi, Suharsiwi; Shofiyah, Siti; Nurmulia, Fatma; Setiyanti, Anis; Rutska, Rutska; Santiago, Paulo Vitor da Silva (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
The purpose of this study is to describe and analyze the development of teaching materials, and the level of feasibility of using technology-based teaching materials in learning Islamic Religious Education. This research is a type of research and development (Research and Development). By using the four-D (4-D) model developed by Thiagarajan (Define, Design, Develop, and Disseminate). The results of this study, according to media and material experts, show that the teaching materials developed have very feasible criteria with an average score of 4.65, both according to media experts and material experts based on their aspect assessment. Meanwhile, according to students' responses, they have an average score of 4.25 with very decent teaching material assessment criteria. Â  Tujuan dari penelitian ini adalah untuk mendeskripsikan dan menganalisis pengembangan bahan ajar, dan tingkat kelayakan penggunaan bahan ajar berbasis teknologi dalam pembelajaran Pendidikan Agama Islam. Penelitian ini merupakan jenis penelitian dan pengembangan (Research and Development). Dengan menggunakan model four-D (4-D) yang dikembangkan oleh Thiagarajan (Define, Design, Develop, and Disseminate). Hasil penelitian ini, menurut ahli media dan ahli materi, menunjukkan bahwa bahan ajar yang dikembangkan memiliki kriteria sangat layak dengan skor rata-rata 4,65, baik menurut ahli media maupun ahli materi berdasarkan aspek penilaian mereka. Sementara itu, menurut respon siswa, bahan ajar tersebut memiliki skor rata-rata 4,25 dengan kriteria penilaian bahan ajar yang sangat layak.